Trophic inferences of the gray triggerfish Balistes capriscus based on stable isotopes analyses, in the Colombian Caribbean (2021)
The demersal fish are a commercial resource of small-scale fisheries of northern Colombian Caribbean. Balistes capriscus is frequently and important in fishing landings, but this species has not economic value and its trophic ecology is unknown. Due to this, the diet was examined using the stomach contents and stable isotopes analysis. The individuals were collected with fish pots during two seasonal research expeditions in May and August of 2018. The δN and δC values were significantly different between size classes, indicating ontogenetic shifts in habitat use and consumption of prey. The δC shows that the triggerfish tends to feed in areas closer to the coast and his source of its origin can possibly change from the pelagic zone when they are juveniles, to the benthic trophic networks in his adulthood. The trophic position mean according to Bayesian inferences and Post's estimates was 2.98 and 3.03 and increased with size. Likewise, isotopic niche width corroborates the ontogenetic shift related with the maturity groups.